Bis‐Calix[4]arenes: From Ligand Design to the Directed Assembly of a Metal–Organic Trigonal Antiprism. Issue 26 (11th May 2016) - Coletta, Marco; McLellan, Ross; Murphy, Paul; Leube, Bernhard T.; Sanz, Sergio; Clowes, Rob; Gagnon, Kevin J.; Teat, Simon J.; Cooper, Andrew I.; Paterson, Martin J.; Brechin, Euan K.; Dalgarno, Scott J.
Abstract: Calix[4]arenes (C[4]s) are versatile platforms for the construction of polymetallic clusters containing paramagnetic metal ions. Synthetic modification at the C[4] methylene bridge allows for the design of bis‐C[4]s that, depending on the linker employed, can be used to either dictate which clusters can be formed or direct the assembly of a new metal–organic polyhedron (MOP). The assembly resulting from the latter approach displays thermal stability and uptake of N2 or H2 gas, confirming that this is a viable route to the synthesis of new, functional supramolecular architectures. Abstract : Synthetic modification at the calix[4]arene (C[4]) methylene bridge offers a unique opportunity to influence cluster‐forming chemistry. The synthesis of xylyl‐tethered bis‐C[4]s and their use as directing species in cluster‐forming reactions is presented. These new ligands have been used to direct the assembly of a previously known Fe III 2 Ln III 2 cluster, as well as a spectacular new metal–organic trigonal antiprism, which also displays thermal stability and uptake of N2 or H2 gas.